DAMPAK PELATIHAN PMBA PADA KADER POSYANDU DALAM MENINGKATKAN STATUS GIZI ANAK STUNTING - Wijayanti, Heny Noor; Fauziah , Afroh (UNIVERSITAS NGUDI WALUYO, 2019)
Background: Optimal feeding for infants and children is an effective intervention in an effort to improve health status and reduce child mortality. The results of monitoring the nutritional status of children in Sleman in 2015 obtained 12.86% stunting, 7.53% underweight, 6.14% overweight and 3.57% wasting. For this reason, efforts to prevent and improve child nutrition problems are needed, one of which is to increase posyandu cadres in growth monitoring and counseling for feeding infants and children through PMBA training. Objective: To determine the impact of PMBA training for Posyandu cadres in improving the nutritional status of stunting children in Sleman District Health Center. Methods: Research Methods: This study uses qualitative methods with informant retrieval techniques by purposive sampling. The main informants were 6 people consisting of posyandu cadres who had PMBA training and triangulation informants totaling 3 people. This research was conducted in the Depok II Health Center area. Data collection techniques using in-depth interview techniques with descriptive analysis. Result: The impact of PMBA training makes cadres able to provide counseling to the community well, can change parenting parents in providing food to babies and children appropriately and correctly according to the rules of balanced nutrition. Conclusion: With PMBA, cadres can reduce and even prevent the incidence of stunting and improve the nutritional status of children under five bymentoring nutrition conscious families. Abstrak : Latar belakang : Pemberian makan pada bayi dan anak yang optimal merupakan intervensi efektif dalam upaya peningkatan status kesehatan dan penurunan angka kematian anak. Hasil pemantauan status gizi balita di Kabupaten Sleman tahun 2015 diperoleh 12,86% stunting, 7,53% underweight, 6,14% overweight dan 3,57% wasting. Untuk itu perlu upaya pencegahan dan perbaikan masalah gizi balita, salah satunya yang dilakukan dengan meningkatkan kader posyandu dalam pemantauan pertumbuhan dan konseling pemberian makanan bayi dan anak melalui pelatihan PMBA. Tujuan : Untuk mengetahui dampak pelatihan PMBA bagi kader Posyandu dalam meningkatkan status gizi anak stunting di Puskesmas Wilayah Kabupaten Sleman. Metode Penelitian : Penelitian ini menggunakan metode kualitatif dengan teknik pengambilan informan secara purposive sampling. Informan utama berjumlah 6 orang yang terdiri dari kader posyandu yang sudah pelatihan PMBA dan informan triangulasi berjumlah 3 orang. Peneitian ini dilakukan di wilayah Puskesmas Depok II. Teknik pengambilan data menggunakan teknik wawancara mendalam dengan analisis secara deskriptif. Hasil : Dampak dari pelatihan PMBA membuat kader bisa memberikan konseling kepada masyarakat dengan baik, dapat mengubah pola asuh orang tua dalam memberikan makan pada bayi dan anak dengan tepat dan benar sesuai aturan gizi seimbang. Kesimpulan : Dengan adanya PMBA, kader bisa mengurangi bahkan mencegah angka kejadian stunting dan meningkatkan status gizi anak balita dengan pendampingan keluarga sadar gizi.